2015
DOI: 10.1073/pnas.1520779112
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1*11and variants of the MHC class II locus are strong risk factors for systemic juvenile idiopathic arthritis

Abstract: Systemic juvenile idiopathic arthritis (sJIA) is an often severe, potentially life-threatening childhood inflammatory disease, the pathophysiology of which is poorly understood. To determine whether genetic variation within the MHC locus on chromosome 6 influences sJIA susceptibility, we performed an association study of 982 children with sJIA and 8,010 healthy control subjects from nine countries. Using meta-analysis of directly observed and imputed SNP genotypes and imputed classic HLA types, we identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(70 citation statements)
references
References 23 publications
2
66
0
2
Order By: Relevance
“…Specifically, oligoarticular JIA (≤ 4 joints), RF-positive polyarticular JIA (≥ 5 joints), and systemic JIA are linked to different HLA alleles. Susceptibility alleles for oligoarticular JIA are HLA-DRB1*08, HLA-DRB1*11 and HLA-DPB1*02:01 202,203 , for RF+ polyarticular JIA are DRB1 SE alleles 204 , and for systemic JIA, HLA-DRB1*11:01 and HLA-DRB1*11:04 172 . The association of some HLA class II alleles with particular phenotypes in JIA provides support for the existence of particular clinical subtypes of JIA 31 .…”
Section: [H2] Disease Subtypesmentioning
confidence: 99%
“…Specifically, oligoarticular JIA (≤ 4 joints), RF-positive polyarticular JIA (≥ 5 joints), and systemic JIA are linked to different HLA alleles. Susceptibility alleles for oligoarticular JIA are HLA-DRB1*08, HLA-DRB1*11 and HLA-DPB1*02:01 202,203 , for RF+ polyarticular JIA are DRB1 SE alleles 204 , and for systemic JIA, HLA-DRB1*11:01 and HLA-DRB1*11:04 172 . The association of some HLA class II alleles with particular phenotypes in JIA provides support for the existence of particular clinical subtypes of JIA 31 .…”
Section: [H2] Disease Subtypesmentioning
confidence: 99%
“…Previously, genome wide association studies (GWAS) of unrelated patients with sJIA did not reveal significant -log 10 p values for the FAMIN locus [9]. Therefore, variants within this gene do not seem to play a role in patients suffering from the common forms of sJIA.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, an association of polymorphisms within the IL1 and IL1R cluster genes [6, 7], the macrophages migration inhibitor factor (MIF) and the IL10 cytokine cluster [8] has previously been described. Furthermore, a current genome wide association study (GWAS) identified the MHC locus as a bona fide susceptibility locus for the phenotype of sJIA [9]. …”
Section: Introductionmentioning
confidence: 99%
“…B. IL-1β, IL-18, IL-6 und der S100-Moleküle) auslöst, und hierdurch eine proinflammatorische Antwort unterhalten wird (2)(3)(4)(5). Es wurden außerdem in den vergangenen Jahren eine Reihe genetischer Assoziationen identifiziert: Zum einen konnten bei sJIA-Polymorphismen innerhalb des IL-1-und IL1R-Clustergens (6, 7) des Makrophagen-Migrationsinhibitorfaktors (MIF) und des IL-10-Zytokin-Clusters (8) nachgewiesen, und zum anderen der MHC-Locus mithilfe einer genomweiten Assoziationsstudie (GWAS) als Suszeptibilitätsort für die sJIA beschrieben werden (9).…”
Section: Hintergrundunclassified